Système des acteurs et stratégie de formulation - Lapierre Olivier (Oléagineux, Corps gras, Lipides, 2005)
Formulation is a central strategy for appropriate protein supply and use. It aims at combining the best answer to animal nutritional requirements together with the economic efficiency of the feed industry. To this end, it is necessary to consider the diverse sources of feed ingredients and to favor the substitution of one raw material by another one whenever it improves the technical or economical performances of the feed. This can be achieved by optimization, which is the key tool of animal feed formulation. The formulation strategy has the potential to respond to many other issues than the technical and economical ones, such as the environmental and safety issues. This wider approach allows us to better appraise the complexity of the production system, which encompasses many interacting agents, and to more efficiently evaluate their respective role and impact on the feed supply.